Comparison between NFC/RFID and bar code system for halal tags identification: Paired sample t-test evaluation - Khosravi, Mohsen; Imtiaz Ali, Najma; Karbasi, Mostafa; Brohi, Imtiaz Ali; Ahmed Shaikh, Irfan; Shah, Asadullah (The Science and Information (SAI) Organization Limited, 2018)
Malaysia is a modern Muslim country where the research on Halal product identification is at the peak. In this study, the authors have developed the mobile applications which is based on Radio Frequency Identification near filed communication RFID/NFC. The author first developed the database based on the data from Jabatan Kemajuan Islam Malaysia JAKIM, which is a Malaysian Halal logo identification authority then the mobile application which uses the near filed communication to detect the Halal food using the Radio Frequency Identification. In this paper authors have performed the experimental analysis by comparing the Bar code system that is compared to parallel time detected by the simple webcam for the Halal Logo Identification and the new developed RFID/NFC mobile applications. Paired sample T-Test was performed by using the SPSS 23.0 version. The results revealed that there is significantly difference between the usability, efficiency, affordability, security and satisfaction. The users are more satisfied with the newly developed mobile application as compared to old halal logo system in Malaysia.